Ensuring Safety and Reliability: An Overview of Lithium-Ion Battery Service Assessment - Cezar Comanescu (Batteries)
Lithium-ion batteries (LIBs) are fundamental to modern technology, powering everything from portable electronics to electric vehicles and large-scale energy storage systems. As their use expands across various industries, ensuring the reliability and safety of these batteries becomes paramount. This review explores the multifaceted aspects of LIB reliability, highlighting recent advancements and ongoing challenges. The importance of safety has been underscored by numerous incidents, such as the well-known smartphone battery explosions and more than 10,000 fires a year at facilities throughout Australia, both linked to LIB failures. These events emphasize the need for robust reliability and safety measures to ensure consistent performance and longevity. Factors like battery chemistry, design, manufacturing, and operating conditions can all influence the reliability of LIBs. Despite their widespread use, the mechanisms of failure, failure rates, and consequences of LIB failures are still not well understood, raising significant safety concerns. Current reliability assessment techniques include experimental methods, computational models, and data-driven approaches. Emerging trends, such as advanced characterization techniques and standardized testing protocols, advocate for improved practices to enhance the reliability and safety of LIBs across all applications.